Different RISC rates in benzoylpyridine-based TADF compounds and their implications for solution-processed OLEDs. (November 2020) - Berenis, Domantas; Kreiza, Gediminas; Juršėnas, Saulius; Kamarauskas, Egidijus; Ruibys, Virginijus; Bobrovas, Olegas; Adomėnas, Povilas; Kazlauskas, Karolis
Abstract: Reverse intersystem crossing (RISC) rate is among the key parameters of TADF compounds affecting triplet upconversion and annihilation processes, and thus determining efficiency roll-off in TADF-OLEDs. Herein, control of RISC rate ( k RISC ) in a series of benzoylpyridine-based TADF compounds via carbazole donor linking positions is demonstrated. Regardless of the similar singlet-triplet energy splitting found in the compounds with meta- or para- carbazole linking topologies, meta- Cz compounds exhibited stronger singlet-triplet state coupling resulting in 10-fold larger k RISC (up to 2 × 10 6 s −1 ) as that in para- Cz counterparts. Different k RISC was shown to have important implications for the solution-processed TADF-OLEDs based on the benzoylpyridines. Explicitly, in the non-doped devices based on neat meta- Cz emissive layers, larger k RISC was crucial for the reduced roll-off. Conversely, in 1.2 wt% rubrene-doped hyperfluorescent devices employing benzoylpyridines as TADF hosts, insignificant roll-off was observed irrespective of k RISC, provided it is above 10 5 s −1 . The obtained results give insight into the possibilities of controlling k RISC in benzoylpyridines and demonstrate its importance for efficiency roll-off of TADF and hyperfluorescent OLEDs. Highlights: New carbazole-benzoylpyridine TADF compounds were synthesized. TADF properties were controlled by donor linking topology. RISC rate affected non-doped OLED performance. No impact of RISC rate was observed for rubrene-doped devices.